The Effectiveness of Total Physical Response and Discovery Learning Method on Students Vocabulary Mastery - Fidella Nur Arofah; Fitri Hilmiyati; Ila Amalia (Wanastra: Jurnal Bahasa dan Sastra, 2023)
This research to find measure between students who are taught using the total physical response method and students who are taught using the discovery learning method in mastering students' vocabulary at the seventh grade of SMPN 6 Cilegon in 2022/2023 academic year. The research methodology is used quantitative method specifically quasi-experimental research design. The instrument used in this research is test. This research involved 33 students in experimental class and 33 students in control class as a sample among the seventh grade of SMPN 6 Cilegon. The research findingresult showed that there is a significant difference between students using total physical response and discovery learning method. Based on the results of the Wilcoxon-test, in experiment group has sig 0.000 < 0.05 and in control group has sig 0.034 < 0.05. It can be concluded that the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The result of this research that the total physical response was effective than discovery learning method in mastering students’ vocabulary at junior high school, espcially at the seventh grade of SMPN 6 Cilegon.